If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6(0) = 6 Multiply -6 * 0 3x + 0 = 6 Anything times zero is zero. 3x + 0 = 6 Reorder the terms: 0 + 3x = 6 Remove the zero: 3x = 6 Solving 3x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 2 Simplifying x = 2
| x-3=2x-5 | | 12=0.5+2.5 | | 2.5r+11=6.5 | | .75f-2=.5f | | 3m=100 | | x+2y=44 | | -25=5g-15 | | 1000.00+150.00x=1300.00 | | -12=2b-30 | | 100/6 | | 1000.00+150.00x=2200.00 | | 10=-3v-8 | | 2n+7=10n-9 | | x^2+236-15x=180 | | 13y=y^2-90 | | onehalf-2=onesixthf | | m/0.3=8 | | w/4+13=21 | | 8Q=24-P | | 2x+4=4x-3 | | 360-x^2-x^2/2=3x | | w/4+13=24 | | 5(a-3)+2a=27 | | 3(4)-6y=6 | | x+y/2=65 | | x-(-17)= | | 3/4x+7=19 | | 1/3(12-6r)= | | x-17= | | 5(a-3)+3m=27 | | (48-12)/4.5=X | | 2a+3(a+4)=-3 |